Proton transfer equilibria, temperature and substituent effects on hydrogen bonded complexes between chloranilic acid and anilines. Issue 3 (2000) - Gohar Gohar, Gamal A. Gamal A.; Habeeb Habeeb, Moustafa M. Moustafa M.
Abstract : The proton transfer equilibrium constants ( K PT ) for 1 : 1 complex formation between Chloranilic Acid (CA) and a series of p - and m ‒substituted anilines have been measured in 1, 4-dioxane spectrophotometrically. The results supported the concept of amine-solvent hydrogen bond formation (short range solvation effect). Beside, this effect, the K PT values were apparently affected by the electron donation power of the aniline ring substituent, which was transmitted to the interaction center via resonance and inductive effects. Linear relationships between K PT and σ-Hammett substituent constants, or p K values for m and p anilines, were obtained verifying the above conclusions. The solute-solvent hydrogen bond formation might increase the reactivity of the aniline nitrogen than would the inductive effect of the alkyl group, in case of CA- N -alkyl aniline complexes. The thermodynamic parameters for the proton transfer complex formation were estimated and it was indicated that the solvent–aniline hydrogen bond formation was preferred in the case of p -substituted aniline complexes more than in the case of the corresponding m ‒isomer. It has been found that the proton transfer process was enthalpy and entropy controlled.